Development of Spatial Distribution Model using GIS to Identify Social Support Index Among Drug-Abuse Inmates - Mohamad, Mahadzirah; Khairul Amri Kamarudin, Mohd; Juahir, Hafizan; Azman Mat Ali, Nor; Karim, Fazida; Badarilah, Nurhikmah; Muhammad, Norhilmi; Syaakir Mohd Ridzuan, Muhammad (International Journal of Engineering and Technology, 2018)
This study was to identify the spatial distribution of Social Support Index (SSI) among drug-abuse inmates throughout Peninsular Malaysia. Factor Analysis (FA) and Discriminant Analysis (DA) were applied to analyses the level of social support (SS) among drug-abuse inmates and develop the spatial model using Geographic Information System (GIS). Five significant index categories were generated from FA: excellent, good, moderate, low and poor Quality of Life Index (QoLi) and the nine of SS variables are expected to be derived from family, friends and other social factor. DA showed each category differed from others in terms of different compositions, stepwise backward and forward modes gave 99.75% correct classification. GIS analysis show the distribution of SSI categorized on family and friends factor were moderately for where the prisoners came. Besides that, Perlis classified as low-level index and Melaka as high-level index of other social factor. The distribution model of SSI in moderately-level showed Jelebu, Sungai Petani, Pengkalan Chepa and Simpang Renggang as the better SS factor to quality of life compared to the Penor, Pahang. The procedures of FA, DA and GIS were used in this study proved the source apportionment of SS and QoLi among drug-abuse inmates in Peninsular Malaysian prisons.Â Â